Screening for inhibitors against SARS-CoV-2 and its variants - Weijing Yuan; Xiaojing Dong; Lan Chen; Xiaobo Lei; Zhuo Zhou; Li Guo; Jianwei Wang (Elsevier, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve, generating new variants that pose a threat to global health; therefore, it is imperative to obtain safe and broad-spectrum antivirals against SARS-CoV-2 and its variants. To this end, we screened compounds for their ability to inhibit viral entry, which is a critical step in virus infection. Twenty compounds that have been previously reported to inhibit SARS-CoV-2 replication were tested by using pseudoviruses containing the spike protein from the original strain (SARS-CoV-2-WH01). The cytotoxicity of these compounds was determined. Furthermore, we identified six compounds with strong antagonistic activity against the WH01 pseudovirus, and low cytotoxicity was identified. These compounds were then evaluated for their efficacy against pseudoviruses expressing the spike protein from B.1.617.2 (Delta) and B.1.1.529 (Omicron), the two most prevalent circulating strains. These assays demonstrated that two phenothiazine compounds, trifluoperazine 2HCl and thioridazine HCl, inhibit the infection of Delta and Omicron pseudoviruses. Finally, we discovered that these two compounds were highly effective against authentic SARS-CoV-2 viruses, including the WH01, Delta, and Omicron strains. Our study identified potential broad-spectrum SARS-CoV-2 inhibitors and provided insights into the development of novel therapeutics.